Fast Antinoise RFID-Aided Medical Care System - Ming-Hour Yang; Jia-Ning Luo (International Journal of Distributed Sensor Networks)
We propose a grouping proof scheme to help the nursing staff on their final check automatically before a medicine round. During the medicine round, even though their RFID reader is offline, our method can generate multiple proofs for each patient and help the medical caretakers follow the five-right policy to correctly administer the drugs to their patients. Besides, because our scheme enables a nurse to target specific group tags during a medicine round, it is able to generate proofs even when the illegitimate tags are on site. We prove that our generated proof is reliable because it can resist most security threats and guarantee the integrity of the proof. Besides, our proposed scheme guarantees anonymity on the RFID tags, so the patients' sensitive information and location privacy can be protected. Last, we run a simulation to show that compared with the related methods our proposed scheme requires the least transmission time and the lowest computation loads to generate a proof.